Overlapping labour market areas based on link communities1. Issue 1 (11th October 2017) - Han, Yicheol; Goetz, Stephan J.
Abstract: Many urban areas around the world have expanded from monocentric to polycentric regions forming larger hierarchical structures. These regions represent functional regions or labour market areas (LMAs) that are classified as groups of counties representing mutually exclusive, non‐overlapping geographies. In practice, however, a county may belong to multiple overlapping LMAs. To model this overlapping across urban hierarchies, we extend the link community method from network theory and apply it to US commuting data. Our proposed approach reliably identifies the LMAs that we would expect to find as well as core and periphery areas within them.